ANALISIS DAMPAK TEKANAN SISTEM HARGA E-KATALOG DAN BIAYA IMPOR BAHAN BAKU TERHADAP STRUKTUR BIAYA, RASIO KEUANGAN, DAN SKOR ALTMAN Z : (STUDI KASUS PADA PT DARYA VARIA LABORATORIA TBK DAN PT KALBE FARMA TBK 2019–2023) - Nugroho, Ari; Faizatun; Putriana, Lies (UNIB Press, 2026)
The e-catalogue pricing system for medicines under Indonesia’s National Health Insurance (JKN) and the high dependence on imported raw materials create major external pressures on the financial performance of local pharmaceutical firms. This study analyses how e-catalogue price pressure and rupiah–US dollar fluctuations relate to cost structure, key financial ratios, and financial distress risk using the modified Altman Z-Score. A descriptive qualitative design was applied to two listed companies, PT Darya Varia Laboratoria Tbk (DVLA) and PT Kalbe Farma Tbk (KLBF) for 2019–2023, using secondary data from audited consolidated financial statements, annual reports, and sustainability reports. Financial ratios and Z-Scores were calculated in Excel and interpreted together with thematic document analysis of adaptive strategies. Results show margin compression, particularly in JKN-related lines, and higher cost exposure when the rupiah depreciated. Nevertheless, both firms remained in the safe zone throughout the period (DVLA Z-Score 6.26-7.45; KLBF 9.82-11.68), indicating strong financial resilience. KLBF’s gross profit margin declined from 45.3% (2019) to 38.8% (2023), while DVLA maintained a relatively stable gross profit margin from 51% (2019) to 54% (2023) but faced rising operating costs. Adaptive strategies, such as OTC diversification, supply-chain integration, foreign rate exchange risk management, and local raw-material initiatives, helped mitigate policy and currency shocks. The study highlights the importance of cost-structure efficiency, foreign-exchange risk controls, and domestic raw-material capability to sustain competitiveness under national pricing regulation and global volatility.